International Education: Alternatives to the Market - Scott, Peter (International Higher Education, 2010)
The widespread assumption that academic mobility and international education are "good things" may need to be tested periodicallyto ensure, first, that the lessons of mass higher education at home have been fully incorporated into concepts of international education; and second, that the lessons of globalization have been factored into policies for international education.